IMPLEMENTASI PERATURAN DAERAH TENTANG PELAYANAN PUBLIK DI KOTA SURABAYA - Windiani Windiani (JURNAL SOSIAL HUMANIORA (JSH), 2010)
This research aim to know about interpretation and implementation low of Public Service in Surabaya. Beside that, to aim for complicated researchs about region law within public service in Surabaya and give in put to decision maker to attitude law of public service in Surabaya. This research do in Surabaya city and take many public officials as informant with snowball sampling model. This is kualitatif research with use diskriptif analysis. Out put of this research show that interpretation of public officials to law of public serveice in Surabaya city is diferents because; First, the law of public service is new, so there is not technical references to interpretation law of  public service. Second, every public service have subject service and character diferences so, interpretation of pubic service become different. Third, there is not thesame of  reference to implementation of low public services. Fourth, there is not change paradigm of public officials  that they should give service not serviced by public. But, in generally, for many official public that’s mean as commitment type of government to increase quality of public service espesialy for Surabaya  citizen. Althougt, consciously that implementation law of public service not opptimaly because many resion: there are not Standart of minimum Services from public services, quality of human resoursches, and carrying capacity of services not good.